Power systems analysis illustrated with matlab and etap - SHERTUKDE, HEMCHANDRA MADHUSUDAN ([Place of publication not identified], PRODUCTIVITY Press, 2018)
Electrical power is harnessed using several energy sources, including coal, hydel, nuclear, solar, and wind. Generated power is needed to be transferred over long distances to support load requirements of customers, viz., residential, industrial, and commercial. This necessitates proper design and analysis of power systems to efficiently control the power flow from one point to the other without delay, disturbance, or interference. Ideal for utility and power system design professionals and students, this book is richly illustrated with MATLAB and Electrical Transient Analysis Program (ETAP) to succinctly illustrate concepts throughout, and includes examples, case studies, and problems. Features Illustrated throughout with MATLAB and ETAP Proper use of positive/negative/zero sequence analysis of a given one-line diagram (OLD) associated with a grid, as well as finger-holding instructions to tackle a power system analysis (PSA) problem for a given OLD of a grid On-line evaluation of power flow, short-circuit analysis, and related PSA for a given OLD Appropriately learn the finer nuances of designing the several components of a PSA, including transmission lines, transformers, generators/motors, and illustrate the corresponding equivalent circuit Case studies from utilities and independent system operators
6.1 Introduction6.2 Node Equations; 6.3 Matrix Partitioning; 6.4 Node Elimination One at a Time; 6.5 Modification of an Existing Bus Impedance Matrix; Problems; 7: Load Flow Analysis; 7.1 Load Flow Solutions and Control; 7.2 Newton-Raphson Method; 7.3 Case of Two Unknown Variables; 7.4 Application of Newton-Raphson Method to Power Flow for n-Buses; 7.5 Newton-Raphson Applied to a Two-Bus System; 7.6 Differentiating Buses; 7.7 Solution Process; Problems; 8: Control of Power into Networks; 9: Underground or Belowground Cables; 9.1 Introduction; 9.2 Electric Stress in a Single-Core Cable
OCLC-licensed vendor bibliographic record.
Keywords: MATLAB; Electric power systems -- Design and construction; Electric power systems -- Computer simulation; TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY / Electronics / General; SCIENCE / Energy